Fruit and Seeds Development and Seed Germination of Andaliman Pepper (Zanthoxylum acanthopodium DC.) - Fahmi, Mochammad; Widajati, Eny; Palupi, Endah Retno; Rostiana, Otih (Department of Agronomy and Horticulture, IPB University, 2026)
Andaliman is a species found in the Lake Toba region of North Sumatra, Indonesia. To determine its optimal harvest time and the length of its physiological maturity, it is necessary to observe fruit development in new locations outside its natural habitat. Andaliman seeds are known for their low germination rates and are classified as endospermic seeds. This study aims to analyze the stages of fruit and seed development, evaluate the effects of seed treatments, and identify the most effective germination test methods for andaliman seeds. Seeds were treated with a 50% H2SO4 solution for 15 min and with a 200 ppm GA3 + 100 ppm kinetin solution for 48 hr. The seeds were then tested using pleated paper and top paper media to assess germination response. Changes in fruit coloration indicated various stages of development: intense yellowish-green at 17 weeks after anthesis, deep yellowish-green at 20 weeks, deep red at 23 weeks, and dark greyish-yellowish-brown at 26 weeks. During development, some fruits experienced embryo abortion, resulting in many empty or wrinkled seeds. The seeds reached physiological maturity at 23 weeks after anthesis, as indicated by a deep red fruit color, increased seed dry weight, and enhanced germination and seed growth rates. The treatment with GA3 and kinetin yielded the highest germination rate of 20%, with the pleated paper method proving to be the most effective for germination testing.